Monoclonal antibody or aspirin desensitization in NSAID-exacerbated respiratory disease (N-ERD)? - Van Broeck, Dorien; Steelant, Brecht; Scadding, Glenis; Hellings, Peter W. (Frontiers in Allergy, 2023)
Nonsteroidal anti-inflammatory drug (NSAID)-exacerbated respiratory disease (N-ERD) is a clinical syndrome characterized by nasal polyposis, asthma, and intolerance to aspirin/NSAID. It affects approximately 15% cases of severe asthma, 10% of nasal polyps and 9% of rhinosinusitis. N-ERD results in associated asthma exacerbations, oral corticosteroids bursts, corticosteroid-dependent disease, and multiple endoscopic sinus surgeries. Unknown influences cause polyp epithelium to release alarmins, such as IL-33 and TSLP. These cytokines activate lymphoid cells, both Th2 and ILC2, to release cytokines such as IL5, IL4 and IL13, resulting in complex type 2 inflammation involving mast cells, eosinophils and platelets. Arachidonic acid released from such cells is metabolized into mediators. N-ERD is characterized by an imbalance in eicosanoid levels, especially CysLTs, PDG and PGE2. Patients with N-ERD present nasal symptoms (congestion, hyposmia/anosmia, nasal discharge) and lower airways symptoms (cough, sneezing, shortness of breath, chest tightness), anosmia, severe hyposmia as well as severe asthma which impacts the quality of life in this disease and leads to safety concerns in patients daily lives. Despite the variety of treatment strategies, the likelihood of recurrence of symptoms is high in patients with N-ERD. The most important strategies for treating N-ERD are listed as following: drug therapies, aspirin desensitization, monoclonal antibodies and other therapies associated. N-ERD treatment remains a major challenge in the current situation. Selecting the appropriate patient for aspirin desensitization, monoclonal antibodies or both is essential. This review provides an overview on aspirin desensitization and biologics in N-ERD and might help in decision making from both the perspective of the physician and patient. Patient characteristics, safety, efficacy, health care costs, but also patient preferences are all factors to take into account when it comes to a choice between biologics or aspirin desensitization.